The Influence of Dynamic Capability on Program Uniqueness and Its Implications for Business Performance through Flexibility Strategy in the Coffee Business - Eva Rachmawati; Vanessa Gaffar; Lili Adi Wibowo; Puspo Dewi Dirgantari (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objectives: The coffee industry is characterized by intense competition, shifting consumer preferences, and vulnerability to external disruptions, creating challenges for businesses aiming to maintain sustainable performance. This study investigates the role of dynamic capabilities in shaping program uniqueness and enhancing business performance, with strategic flexibility examined as a mediating factor.Methodology: Adopting a quantitative research design, the study utilizes a structured questionnaire distributed among decision-makers in small and medium-sized coffee enterprises across Indonesia, and analyzes the data using Structural Equation Modeling with AMOS.Finding: The findings provide both theoretical advancement and practical implications for SMEs in the coffee sector by highlighting the importance of resource orchestration and adaptive strategies in sustaining competitive advantage. This research contributes to the broader discourse on strategic management and SME development, offering valuable insights for academics, practitioners, and policymakers aiming to enhance resilience and innovation in dynamic industry environments. Bottom of FormConclusion: The results demonstrate that dynamic capabilities specifically sensing, seizing, and reconfiguring resources positively influence the development of unique programs and contribute to improved business outcomes. Furthermore, the presence of a flexibility strategy significantly mediates the effect of dynamic capabilities, enabling firms to adapt more effectively to environmental changes and align their strategic initiatives with market demands. By integrating the Conservation of Resources (COR) theory into the dynamic capabilities framework, this study offers a novel theoretical perspective on how firms can protect, allocate, and optimize resources under conditions of uncertainty.